An epidemiological investigation of gastrointestinal parasites of small ruminants in Tangail, Bangladesh - Rahman, Md Atikur; Labony, Sharmin Shahid; Dey, Anita Rani; Alam, Mohammad Zahangir (Journal of the Bangladesh Agricultural University, 2017)
Gastrointestinal (GI) parasitism is anegregious problem in small ruminant production system due to is impact on growth and associated cost of control measures. An epidemiological study was conducted to investigate the prevalence of gastrointestinal parasites of small ruminants from different areas of Madhupur, Tangail. The stool samples were collected from a total of 426 goats and sheep from study areas. Specimens were subjected to Stoll’s ova counting technique and the overall prevalence of gastrointestinal parasitic infection was found 63.4%. Overall prevalence of nematodes, cestodes, trematodes and protozoa was 52.11%, 2.11%, 36.62% and 10.33%, respectively. The prevalence of parasites were variable with Fasciola spp. (8.45%), Paramphistomum spp. (28.17%), Monieziaspp. (2.11%), Haemonchus spp. (31.22%), Trichurisspp. (1.17%), Oesophagostomum spp. (10.80%), Strongyloides spp. (4.93%), Trichostrongylus spp. (2.35%), Bunostomum spp. (1.64%), Eimeria spp. (24%) and Balantidium spp. (6.34%). Parasitic ova counts in male and female exhibited no significant variations (p>0.05) between them. The infection was significantly higher (65.11%) in adult than in young (58.09%). No significant (p>0.05) variation was observed in infection rates between goats (64.09%) and sheep (60.67%). Seasonal variation was found significant between rainy (72.44%), winter (56.72%) and summer (61.82%) seasons. Animals with poor body conditions (74.67%) were mostly affected compared to those with moderate (62.38%) and good (39.00%) body conditions. Further attempt is necessary for a structured surveillance and monitoring of GI parasites to formulate effective control measures. J. Bangladesh Agril. Univ. 15(2): 255-259, December 2017